P9 The interaction of hMSC and HNSCC under hypoxic and normoxic circumstances in vitro. Issue 5 (May 2015) - Scherzad, A.; Hackenberg, S.; Kleinsasser, N.
Abstract : Introduction: Human mesenchymal stem cells (hMSC) have a strong migration tendency towards cancer with the capacity to integrate directly into the tumor. Therefore, several studies have suggested hMSC as an appropriate candidate for drug delivery therapy. However, interactions between hMSC and cancer are ambiguous. Some studies show tumor progression and enhancement of tumor metastatic potential by hMSC. Since solid tumors exhibit extensive hypoxic regions, the interaction between cancer and hMSC and hypoxic conditions is of specific interest. Hence, the aim of the present study was to investigate the effect of hMSC on HNSCC cell lines including morphological characteristics, migration capability, angiogenesis as well as the paracrine cytokine secretion in vitro and the influence of hypoxia on these interactions. Material: The dot-blot assay, annexin V-propidium iodide test, ELISA, western blot as well as cell invasion assay were investigated. Results: The dot-blot assay revealed a secretion of several cytokines responsible for cell motility, inflammation as well as angiogenesis by hMSC. There was enhancement of Interleukin-6 (IL-6) and Monocyte chemoattractant protein-1 (MCP-1) after cultivation in hypoxic atmosphere. hMSC improved the tumor cell proliferation. This was mediated via an activation of Erk1/2. The addition of anti-IL6 blocked this cell proliferation enhancement. Tumor cell motility was enhanced after cultivation with hMSC. There were no differences in cancer cell motility after co-cultivation with hypoxic and normoxic hMSC. hMSC induced tube like structures in human umbilical vein endothelial cells (HUVEC) indicating pro-angiogenic activity. This was counteracted significantly after differentiation of hMSC into adipocytes and osteocytes. Conclusion: Our results revealed distinct protumorigenic effects of hMSC. Thus the use of hMSC as a potential vehicle for cancer therapy should be discussed critically.